An R package for modelling actual, potential and reference evapotranspiration. (April 2016) - Guo, Danlu; Westra, Seth; Maier, Holger R.
Abstract: Evapotranspiration (ET) is a vital component of the hydrological cycle and there are a large number of alternative models for representing ET processes. However, implementing ET models in a consistent manner is difficult due to the significant diversity in process representations, assumptions, nomenclature, terminology, units and data requirements. An R package is therefore introduced to estimate actual, potential and reference ET using 17 well-known models. Data input is flexible, and customized data checking and pre-processing methods are provided. Results are presented as summary text and plots. Comparisons of alternative ET estimates can be visualized for multiple models, and alternative input data sets. The ET estimates also can be exported for further analysis, and used as input to rainfall-runoff models. Highlights: An R package has been developed to implement multiple ET models in a consistent way. The package features flexibility in ET model choice and climate data input. The package can greatly assist ensemble modelling of ET.